Recent Challenges of the Ecosystems Services Approach from an Interdisciplinary Point of View - Kühne, Olaf; Duttmann, Rainer (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
The ecosystem services approach has attracted tremendous attention from policymaking, planning and interdisciplinary sciences over the last decades. Despite its broad acknowledgement worldwide, there are a number of well-known conceptual and methodological limitations that impair its use and practical operationalisation. A brief discussion of these deficits is conducted from the integrated perspective of natural and social sciences. The paper then critically addresses the question of whether and to what extent the diversity, complexity and hybridity of the human-nature context should be shaped into a uniform scheme, disregarding the differing scales of the social, economic and ecological processes, functions and the trade-offs between them.